Interdisciplinarity in high school integrated to a technical computing school: experience report of the biosoc project - Santana, Ronaldo Santos; Martins, Eledir da Cruz; Franzolin, Fernanda (Revista Hipótese, 2018)
this article aims to report an experience regarding the implementation of an interdisciplinary study carried out in a high school integrated to a Technical Computing School. The data were collected from teacher evaluation instruments and reflections on the practical lesson. After analyzing the results, the development of conceptual, procedural and attitudinal contents by the students and a collaborative study by the teachers were perceived.